Pelatihan Akuntansi bagi Komunitas Usaha Ekonomi Kreatif Kayoetangan Heritage Kota Malang: Optimalisasi Media Daring - Zahroh Zainal Abidin; Maria Goretti Wi Endang; Dwiatmanto Dwiatmanto; Raden Rustam Hidayat; Rachma Bhakti Utami (University of Merdeka Malang, 2021)
Understanding and preparing basic financial reports is essential and necessary for every entrepreneur. This Community Service Activity is essential to do, considering that not many members of the Komunitas Usaha Ekonomi Kreatif Kayoetangan Heritage of Malang City have made financial records for their business. A total of 27 members and administrators of the Komunitas Usaha Ekonomi Kreatif Kayoetangan Heritage participated in this training. The main purpose of this community service activity is to provide simple training on theapreparation of basic accounting financialareports, both for service companies and trading companies. The lecture method is used in this community service. Unfortunately, pandemic conditions hampered the implementation of this training. Researchers then used online or online methods as a training solution amid a pandemic. The training results showed that the participants were enthusiastic about participating in this training, which was shown by the participants being active in conducting discussions. The participants’ assessment of the training activities was excellent. For training and community service in the future, assistance should be provided to training participants to implement financial reports for entrepreneurs fully.DOI: https://doi.org/10.26905/abdimas.v6i2.5161